FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS PADA PERUSAHAAN HEALTHCARE DI INDONESIA - CHERYN EDREA; HENDRA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The purpose of this study is to examine the internal factors that influence the profitability of companies in the Healthcare industry in Indonesia. The research data consist of secondary data obtained from the financial statements of Healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. This study employs a quantitative approach with a purposive sampling method, resulting in 12 companies that meet the criteria over a span of 6 years, producing 72 data observations. EViews 12 software is used to conduct panel data analysis, including descriptive statistics, model selection, classical assumption tests, and panel data regression. The results show that only the operational efficiency variable has a positive significant effect on profitability. Meanwhile, variables such as firm size, financial leverage, net working capital, liquidity, and equity multiplier do not have a significant effect on profitability.